Dental students' perceptions of the long case. (25th September 2021) - Paul, Natasha Lily; Adam, Lee A.; Moffat, Susan M.
Abstract: Introduction: The long case examination is used to assess clinical competency in dental education. However, the academic literature, much of which is in medical education, highlights concerns regarding the relevancy and authenticity of the long case. To date, dental students' experiences of the long case have been under‐researched. This study examines students' experiences and perceptions of the long case examination at an Australasian dental school. Materials and Methods: This study was a qualitative investigation. Students participated in interviews to discuss their perceptions and experiences of the long case examination. The interviews were voice‐recorded and transcribed, and a thematic inductive analysis was undertaken. Results: Three main themes emerged from the data: stress, where students described stressors before, during and after the long case; fairness, where students positioned the long case as either fair or not fair; and confusion, where students spoke about their perceived lack of understanding of the examination process and procedures. Conclusion: The concerns students raised regarding stress, fairness and confusion are considered and ways in which the long case might be developed in order to support students' learning are presented. Alternative structures or practices that might be explored include greater calibration of examiners and cases, and enhancements to how students are prepared for and prepare for the examination. The results of this research will inform ongoing development of assessment practices.